Kredit Bermasalah Untuk Meningkatkan Profitabilitas Busn Non Devisa Go Public - Agustina, Widia; Surachim, Ahim (Universitas Pendidikan Indonesia, 2017)
The purpose of this research is to study the NPL research and Profitability. This research was carried out in a period of five years, for banks, in the design of the research framework used is historical data, against samples without random using historical data, then the design of this study uses a combined design. This study uses descriptive and verification methods with hypothesis testing methods and data analysis techniques using panel data regression. The Findings of Problem Credit refers to Profitability. This difference is determined in the independent variables, objects and research methods, participation and research samples, research period, measurement tools and research results, as well as sources of theory and foreign journals and foreign books and research results